NARRATOLOGISCHE ANALYSE DES GORGIAS-ROMANS „VERIPHANTORS BETROGENER FRONTALBO” - Zoltán MIKÓ (Studia Universitatis Babeş-Bolyai. Philologia, 2021)
A Narratological Analysis of the Novel Veriphantors Betrogener Frontalbo by Johann Gorgias. Veriphantors Betrogener Frontalbo is the most important novel by the German-Transylvanian writer Johann Gorgias. It represents the pinnacle of his poetic œuvre, since earlier texts often still consist of few plot elements, and Veriphantors Buhlende Jungfer is a text that is not yet particularly well structured. The educational intent of Gorgias’s earlier texts can seem quite offensive today, as the reader is often bombarded with general rules, commonplaces, and moralizing examples drawn from life after a small plot point. In the narratological analysis, the relationship of the narrated time and the narrative time or pace are examined first. Furthermore, the sequence of events presented, the length of the presentation of incidents (duration), and the “repetition relations” in which “the narrated and the narration” stand, are identified and differentiated.